Accelerating innovative finance for sustainable rice - Siantonas, Tony; Reddy, Matthew; Dimovska, Donika (World Business Council for Sustainable Development, Global Environment Facility, & the Earth Security Group, 2020)
Webinar on “Accelerating innovative finance for sustainable rice” held on February 18/19 2020, hosted by the Sustainable Rice Landscapes Initiative and the Global Environment Facility (GEF). Over 65 people participated during the two webinars.